MicroRNA High Throughput Loss-of-Function Screening Reveals an Oncogenic Role for miR-21-5p in Hodgkin Lymphoma - Yuan, Ye; Niu, Fubiao; Nolte, Ilja M.; Koerts, Jasper; de Jong, Debora; Rutgers, Bea; Osinga, Jan; Azkanaz, Maria; Terpstra, Martijn; Bystrykh, Leonid; Diepstra, Arjan; Visser, Lydia; et al. (Cellular physiology and biochemistry, 2018)
Background/Aims: Classical Hodgkin lymphoma (cHL) is among the most frequent lymphoma subtypes. The tumor cells originate from crippled germinal center (GC)-B cells that escaped from apoptosis. MicroRNAs (miRNAs) play important roles in B-cell maturation and aberrant expression of miRNAs contributes to the pathogenesis of cHL. Our aim was to identify oncogenic miRNAs relevant for growth of cHL using a high-throughput screening approach. Methods: A lentiviral pool of 63 miRNA inhibition constructs was used to identify miRNAs essential to cell growth in three cHL cell lines in duplicate. As a negative control we also infected cHL cell lines with a lentiviral barcoded empty vector pool consisting of 222 constructs. The abundance of individual constructs was followed over time by a next generation sequencing approach. The effect on growth was confirmed using individual GFP competition assays and on apoptosis using Annexin-V staining. Our previously published Argonaute 2 (Ago2) immunoprecipitation (IP) data were used to identify target genes relevant for cell growth / apoptosis. Luciferase assays and western blotting were performed to confirm targeting by miRNAs. Results: Four miRNA inhibition constructs, i.e. miR-449a-5p, miR-625-5p, let-7f-2-3p and miR-21-5p, showed a significant decrease in abundance in at least 4 of 6 infections. In contrast, none of the empty vector constructs showed a significant decrease in abundance in 3 or more of the 6 infections. The most abundantly expressed miRNA, i.e. miR-21-5p, showed significantly higher expression levels in cHL compared to GC-B cells. GFP competition assays confirmed the negative effect of miR-21-5p inhibition on HL cell growth. Annexin-V staining of cells infected with miR-21-5p inhibitor indicated a significant increase in apoptosis at day 7 and 9 after viral infection, consistent with the decrease in growth. Four miR-21-5p cell growth- and apoptosis-associated targets were AGO2-IP enriched in cHL cell lines and showed a significant decrease in expression in cHL cell lines in comparison to normal GC-B cells. For the two most abundantly expressed, i.e. BTG2 and PELI1, we confirmed targeting by miR-21-5p using luciferase assays and for PELI1 we also confirmed this at the protein level by western blotting. Conclusion: Using a miRNA loss-of-function high-throughput screen we identified four miRNAs with oncogenic effects in cHL and validated the results for the in cHL abundantly expressed miR-21-5p. MiR-21-5p is upregulated in cHL compared to GC-B cells and protects cHL cells from apoptosis possibly via targeting BTG2 and PELI1.